Feasibility studies on anaerobic co-digestion of food waste, brown water and cultured milk - Ho, Lip Teng. (2013)
Over the years, Singapore’s waste generation has been increasing. As of 2010, a total of 6.52 million tons (1250 kg per person) of waste has been generated as compared to 2.8 million tons generated in 1998. Much attention is been given to recycling for waste reduction. However, these recycling programs focuses more on the industrial waste and construction debris. One of the wastes for which is increasingly generated overtime due to higher population influx is food waste. Currently, there is no measure and plan being discussed to enhance food waste (FW) recycling by the government and all food waste generated were sent for incineration. This could probably be due to the lack of knowledge and research in making FW recycling economic viable. As such, this has led to the conductance of study on the feasibility of introducing commercially available cultured milk products (containing probiotics) that may ultimately become food waste when expiry date is met.